Готовність медіапростору України та суспільства брати участь в інтелектуальній грі - Благовірна, Наталія Богданівна; Blahovirna, N.B. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Здійснено спробу дослідити причини та наслідки тематичного одноголосся медіапростору України. На реальних прикладах доведено поверховість сучасного медіапродукту. Найактивніше представлена політична тематика. Визнано, що медіа мимоволі реконструюють дійсність, нівелюючи прагнення аудиторії до пізнання навколишнього світу, занижують здатність до верифікації представленої подієвості. Стверджується, що описові тексти ЗМІ не здатні проаналізувати значення тих чи інших подій, вмотивувати важливість розгляду непопулярних тем, закріплюють на рівні щоденного нерефлексивного побуту інфантильність та несвідомість аудиторії. Серед основних причин названо: відсутність розгалуженої мережі спеціалізованих інформаційних агентств, використання «прес-релізних» джерел, небажання журналістів на загал замислюватися над глобальними впливами власної професії, їх низький професійний рівень, падіння соціального статусу редактора. Водночас обґрунтовано необхідність вибудовувати професійну ідентичність журналіста на засадах моральності, інтелекту, що урізноманітнить форми публічної репрезентації. An attempt was made to investigate the causes and consequences of narrowing media-text’s thematic spectrum, so that certain judgments are not highlighted while others are widely replicated. In real examples superficiality of modern media product Ukraine was proved. Inventorization of thematic range of messages has detected a tendency toward political subjects, which is seen as an attempt to describe of «here-and-now-reality», without any efforts to reach common problems. Ukrainian cultural, scientific and educational problems in media-texts are prejudiced. Narrowing information space to a few top themes was considered as an attempt to censor the cognitive capabilities of the consumer. It is indicated that the media unconsciously reconstruct reality, and leveling the audience’s desire to knowledge, understate the ability to verificate eventfulness. Media-texts are not able to analyze the meaning of certain events, do not motivate the importance of unpopular topics, they fix audience’s infantilism and ignorance. Is alleged that the journalism should not only inform about the present, but to determine it, thus modeling the future through the prism of morality, by updating science as the laboratories of meanings, catalyze the evolution of media audience from mechanical consumers to thoughtful consumers, instead journalism today lack the appropriate knowledge and critical analysis. It is noted that journalism should see opportunities to balance the interests of the commercialization of the industry and increasing intellectual ability of audience, and what is the most important – to see their own role in this balancing, that detects and enhance the ability of competent decisions. At the same time it is stated that editor's social status is lowered today in Ukraine, though they are able to improve the quality of any media, transforming the product of individual authorship to the consumer products.
Preparedness of Ukrainian media space and society to participate in the intellectual game
Keywords: медіапростір; media space; медіатекст; media-text; тематика; topics; прес-реліз; news release; журналіст; journalist; моральність; morality; інтелект; intelligence; редактор; editor